The high costs of publishing in scopus-indexed journals pose significant challenges for researchers in developing nations - Ugo Okolie; Anthony Nwokolobia (Qualitative Research of Business and Social Sciences, 2025)
In recent years, publications indexed in Scopus have become an essential benchmark for assessing institutional performance and academic quality. Academic institutions and regulatory agencies use these standards to evaluate research quality, institutional standing, and global recognition. The emphasis on Scopus-indexed publications as a quality marker increases the cost of academic research and discredits work from disadvantaged nations and institutions. This study illustrates the difficulties researchers in emerging nations face when publishing in Scopus-indexed journals due to the high fees involved. This study employed content analysis and a qualitative research approach. This study concluded that Scopus-indexed platforms enable academics to publish their work, network with peers, and remain current with developments in their field. Academic collaboration and networking can result in new publications and research initiatives. Nonetheless, many scholars and institutions continue to encounter difficulties due to the high cost of publishing in Scopus-indexed journals, particularly in developing nations.